Comparsion of two intervention programmes in young female players in European handball - with and without ankle disc - Wedderkop, N.; Kaltoft, M.; Holm, R.; Froberg, K. (Scandinavian Journal of Medicine & Science in Sports, 2003)
The prevention of injuries in all sports calls for a structured plan. The plan consists, as earlier described, of four steps. We have previously presented studies incorporating all four steps. The studies have shown that it is possible to prevent most injuries in young female players in European handball by applying a training programme combining the use of an ankle disc with functional strength training. In the previous studies we were not able to discriminate whether the preventive effect was due to the functional strength training or the training with the ankle disc. The aim of this study was to compare a programme with ankle disc and functional strength training with a programme with functional strength training only. Twenty handball teams were asked to participate, and 16 of 20 handball teams agreed to participate. The teams were cluster randomised to either the programme with or without an ankle disc. The group using the programme without the ankle disc had a significantly higher number of traumatic injuries (16 vs. 6). The incidences of traumatic injuries in the ankle disc group were 2.4 (95% CI 0.7; 6.2) injuries per 1000 h of match and 0.2 (95% CI 0.02; 0.7) injuries per 1000 h of practice. In the group without ankle disc the incidences were 6.9 (95% CI 3.3; 12.7) injuries per 1000 h of match and 0.6 (95% CI 0.2; 1.3) injuries per 1000 h of practice. A significantly higher multivariate odds ratio (4.8) was found in the group not using the ankle disc. In addition the group using the ankle disc had significantly fewer moderate and major injuries. By adding ankle disc training to a training programme with functional strength training, it is possible to reduce the number of injuries significantly, especially the number of moderate and major injuries.